Therapeutic potential of TRIM family proteins in gastric cancer: from signaling pathway regulation to precision targeting strategies - Zhao, Caiqing; Qi, Jialing; Zhang, Zhenze; Feng, Qi; Fang, Ziling; Fang, Nian (Frontiers in Oncology, 2025)
Gastric cancer (GC) is a globally prevalent malignant tumor, causing approximately 770,000 deaths in 2020, ranking fourth among all cancers. The tripartite motif (TRIM) protein family is involved in various cellular regulations and has become a key player in the pathogenesis of gastric cancer. This review explores the therapeutic potential of TRIM proteins in gastric cancer, from signaling pathway regulation to precision targeting strategies. Structurally, there are differences in the C-terminal domain of TRIM proteins, which determine their subgroup classification and substrate recognition. Functionally, they regulate multiple signaling pathways that are crucial for the development of gastric cancer. Clinically, many TRIM proteins serve as promising diagnostic and prognostic biomarkers. In terms of therapy, targeting TRIM proteins holds great potential. Strategies include developing small molecule inhibitors targeting specific TRIM domains, such as inhibitors targeting the bromodomain of TRIM24, and exploring PROTAC technology to degrade oncogenic TRIM proteins. Combination immunotherapy targeting TRIM-related pathways may also provide new therapeutic options. However, challenges persist, Including limited understanding of heterotypic polyubiquitination targets/functions of TRIM proteins, insufficient mechanistic/epidemiological insights into their immunomodulatory roles in the tumor microenvironment, underdeveloped TRIM inhibitors for gastric cancer, unevaluated pharmacokinetics/toxicity of inhibitors in preclinical models, and the need to construct complete TRIM biological systems. In summary, TRIM proteins are deeply involved in the biological processes of gastric cancer, and understanding their functions and regulation could lead to the development of more effective precision targeting strategies for gastric cancer treatment.